Promoting asthma prevention and control through vitamin D supplementation at Zainul Hasan Genggong Islamic Boarding School - Donastin, Adyan; Dwiyanu, Paul Agus; Agustina, Titin Sholihah; Muahammad, Akbar Reza; Istiqomah, Ahla Nurul (Indonesia Berdaya, 2026)
Vitamin D (VitD) has been studied for its role in the immune system, particularly in regulating the body's inflammatory response. Vitamin D deficiency can increase the risk of respiratory tract infections, which can trigger asthma exacerbations. In asthma patients, VitD can act as an immunomodulator in respiratory epithelial cells. The objective of this community service program is to increase students' knowledge about the benefits of vitamin D supplementation in the recognition and management of asthma among students at the Zainul Hasan Genggong Islamic boarding school in Probolinggo. This community service project used an observational analytical method to process questionnaire data. The participants were 40 male and female students at Zainul Hasan Genggong Islamic boarding school. This activity was conducted using a lecture, discussion, and question-and-answer approach. The results of the Wilcoxon signed-rank test showed an increase in the students' knowledge, with a pre-test average score of 30 and a post-test average score of 65, indicating a significant increase (p-value 0.001). The conclusion drawn is that students can understand asthma and the role of vitamin D supplementation in asthma management after receiving counseling, and it is hoped this education will encourage students to adopt healthy lifestyles, recognize asthma symptoms early, and take appropriate action.